Predictors of Knee Arthrofibrosis and Outcomes after Arthroscopic Lysis of Adhesions following Ligamentous Reconstruction: A Retrospective Case–Control Study with Over Two Years' Average Follow-Up - Bodendorfer, Blake M.; Keeling, Laura E.; Michaelson, Evan M.; Shu, Henry T.; Apseloff, Nicholas A.; Spratt, James D.; Malone, Patrick S.; Argintar, Evan H. (The Journal of Knee Surgery, 2019)
Arthrofibrosis can be a devastating complication after ligamentous knee reconstruction. Beyond early range of motion (ROM), manipulation under anesthesia (MUA) and arthroscopic lysis of adhesions (LOAs) are the most frequently employed interventions for the condition. There is a paucity of data regarding predictive factors of arthrofibrosis requiring MUA and LOA, and even less data regarding changes in validated patient-reported outcome measures following the procedure. A retrospective case–control study was performed at an academic, urban Level I trauma center of patients that developed arthrofibrosis requiring MUA and LOA following ligamentous reconstruction. The indication for LOA was failure to achieve a 90° arc of ROM by 6 weeks. Seventeen cases and 141 controls were identified. Follow-up for cases was 26.9 ± 17.1 months (mean ± standard deviation). Time from initial reconstruction to LOA was 75.2 ± 27.9 days. Cases had higher body mass indices by a mean of 2.9 (p = 0.024). The most significant risk factors for stiffness were concomitant anterior cruciate ligament, posterior cruciate ligament, and posterolateral corner/lateral collateral ligament injury (odds ratio [OR], 17.08), knee dislocation (OR, 12.84), and use of an external fixator (OR, 12.81, 95% confidence interval [CI], 3.03–54.20) (all p < 0.0026). Mean Knee Injury and Osteoarthritis Outcome Scores, Western Ontario and McMaster Universities Osteoarthritis Indices, and International Knee Documentation Committee scores improved by 47.5, 50.5, and 47.3% (all p < 0.0038), respectively. All patients reported improvement in pain, with maximum daily pain scores improving by a mean of 4.1 points on the Numeric Pain Rating Scale (p < 0.001). Mean ROM arc improved by 38.8° (p < 0.001). All 17 cases were satisfied with the procedure. Twelve cases (70.59%) reported a full return to preinjury level of activity. No factors were identified that predicted success from the procedure, likely due to inadequate sample size. Arthrofibrosis following knee injury and ligamentous reconstruction can be predicted by the severity of injury and early intervention with MUA and arthroscopic LOA can lead to a satisfactory outcome for the patient.
Keywords: arthrofibrosis; lysis of adhesions; manipulation under anesthesia; ligamentous reconstruction; knee